Kto się boi Krajewskich? Narodziny dyskursu antykomunistycznego w polskim polu sztuki lat 80. - Rohozińska, Zofia (Artium Quaestiones, 2024)
Helena and Juliusz Krajewski were iconic figures of Polish socialist realism who, unlike the entire generation of their contemporary artists, never renounced this trend. The purpose of the article is to show that the art field’s changing approach toward those artists (and with them to socialist realism in general) over the subsequent decades became a symptom of the transformation of the hegemonic discourse. The analysis was conducted based on the decade of the 1980s and selected texts of art criticism of that time. The article is divided into three parts, corresponding to three narratives functioning at that time: (1) Party discourse still immersed in the socialist ideological universe; (2) Party discourse as an outcome of the transformational processes already beginning at that time and reflected the liberalization processes of cultural policy; (3) the discourse of full discreditation of the previous system with a deep critique of the symbol of its functioning, which was socialist realism. The article shows how the transformation of the art field took place between 1980 and 1988 – the socialist system was completely discredited, and the capitalist system, in turn, was naturalized.